Entre os muros e as redes: o florescimento das direitas nas mídias no Brasil (2013 – 2018) - Sobral, Mayara Alves Ferreira (2022)
This research intends to raise questions about the advance of right-wing thinking in Brazil, especially in social media in recent years (2013-2018). The occupation of cyber territories for the consolidation of political strategies, from conservatism to extremism conducted by the right-wingers, flourished mainly with the advent of the June Days of 2013 and ends with the election of Bolsonaro as president. Social media has emerged as an important pillar of 21st century media and information dissemination using the strategies of advertising used during the 20th century to influence people. Social media are no longer merely a cultural apparatus, but weave political, economic, and social influences. The research was guided by methods of understanding the history of the present time through the digital perspective, analyses of the rhetoric of discourse in newspapers; videos and social media posts built the historiographical analysis of the research